The Effect of the Mind Mapping Learning Model Assisted by Limas Traditional House Media on the Learning Outcomes of Fourth Grade Students - Rizki Ramadhan; Kiki Aryaningrum; Budi Utomo (Civiliza Publishing, Indonesia., 2026)
Science learning in elementary schools requires innovative and engaging instructional approaches. Integrating local cultural media into learning can enhance students' understanding and learning outcomes. This study aims to determine the effect of the Mind Mapping learning model assisted by the Limas Traditional House media on the science learning outcomes of fourth-grade students at SD Negeri 81 Palembang. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of Class IV B as the experimental group and Class IV D as the control group. Data were collected through pretests and posttests and analyzed using the Shapiro–Wilk normality test, Levene’s homogeneity test, and the Independent Sample t-test. The findings revealed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the experimental and control groups. Students taught using the Mind Mapping model assisted by the Limas Traditional House media achieved higher learning outcomes than those who received conventional instruction. In conclusion, integrating the Mind Mapping learning model with local culture-based media creates more active, contextual, and meaningful learning experiences, thereby improving students' understanding of science concepts and enhancing their learning outcomes in elementary schools.